A general performance calculation model of journal bearing using unified coordinate system. Issue 4 (8th May 2018) - Zhu, Aibin; Wu, Hongling; Yang, Yulei; He, Shengli
Abstract : Purpose: Because of the various geometric descriptions of different bearing types, performance calculation of journal bearing is complicated, and is difficult in traditional model. This paper aims to simplify the calculation of the journal bearing performance, and to reduce the workload. Design/methodology/approach: On the basis of previous research, a general performance calculation model of journal bearing is proposed in this paper. Eccentricity ratio and attitude angle of axis to each pad are calculated by coordinates of spindle center and each pad center by establishing the unified coordinate system. The surface deformation of journal bearing is taken into consideration, and a correction value is added to the dimensionless oil film thickness. Findings: The performance calculation results of various fix-pad and tilting-pad journal bearings match the results of the existing references very well, revealing the validity of the model. The general model can greatly reduce programming workload, and increase adaptability to different bearings. Originality/value: Geometric descriptions of both fix-pad and tilting-pad journal bearings are unified in this model, which can be applied to both standard and non-standard journal bearings with different preload ratios. In addition, due to the unification of different bearings types, this model is more conducive to performance comparison among different bearing types, and promotes the development of new structural forms for journal bearings.